Perancangan Komik Penjara Masa Depan Bahayanya Narkoba Bagi Remaja - Ridho Sulin Mahendra; Dini Faisal (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
The phenomenon of drugs is becoming more and more public figures and famous artists are also involved. This also resulted in the vulnerability of drug issues among adolescents. The lack of attention from teachers and parents is an important problem because it can threaten the lives of the younger generation themselves in the future. To overcome the deviant behavior of the community, the authors created a solution to this problem by presenting a fictitious work about the dangers of drugs for teenagers through creative media, namely the printed comic "Prison of the Future". This comic is intended as an educational and innovative media that can inform about the dangers of drugs and is a preventive measure so that drug abuse does not occur in the current generation. This work uses the 5W+1H (What, When, Where, Who, Why, and How) analysis method of literature, journal and internet studies. And also the data design method used is the 4D (four-D) design method including Define, Design, Develop & Disseminate (definition, design, development and deployment). The feasibility test of the design of the future prison comic book can be seen in terms of panel layout, composition, illustrations, word balloons, text, stories as well as comic principles and visual communication designs that are suitable and printable.